Alcohol consumption among Nepalese women of reproductive age predictors, anxiety and depression in pregnancy and postpartum period: alcohol consumption among women in Nepal. - Aryal,Krishna Kumar (2017)
SUMMARY: Background: Alcohol consumption is one of the leading risk factors for death and disability worldwide. Harmful use of alcohol is one of the four major behavioral risk factors of main non-communicable disease - cardiovascular diseases, chronic respiratory diseases, cancer and diabetes. On the other hand, alcohol when consumed by women during peri conceptional period also has significant impact on other health conditions including reproductive health of a women with a serious effect on the to be borne fetus. A substantial proportion of women in Nepal consume alcohol and homebrewed alcoholic beverages are the most common type of alcohol consumed. Alcohol is a part of tradition and culture in Nepal and evidences suggest even low to moderate dose of alcohol has impacts on the birth outcomes. This study aimed at exploring different aspects of alcohol consumption by women with a focus on alcohol consumption by women of reproductive age as well as alcohol consumption during pregnancy and postpartum period. In addition, this study also looked into predictors of alcohol consumption, ethanol concentration in Nepalese home brewed alcoholic beverages, as well as anxiety and depression among pregnant women and mothers with children under one year. Methods: This PHD thesis is a result of two studies leading to four articles. First study was nationally representative household survey intended to capture alcohol consumption behavior among 9000 married women of reproductive age 915 to 49 years).In this, we also collected 284 alcohol (home brewed alcoholic beverages) samples from 300 clusters selected for the national survey from across the country. Second study was carried out in a mountainous district of Nepal ( Sindupalchowk) , where majority of the population is made up by the Janajati ethnic groups, to capture alcohol consumption during pregnancy and postpartum period as well anxiety and depression among those women using Hopkins Symptoms Check List(HSCL) along with the semi structured questionnaire. In this study, we interviewed 778 women(pregnant or mothers with children under one year) from 12 Village Development Committees in the selected district and this district had highest prevalence of alcohol consumption among women in the national survey. Descriptive as well as inferential statistics were drawn through appropriate methods using SPSS and STATA statistical software. Results: Readily available home brewed alcoholic beverages in practice were mainly of two types "Distilled" (local Raksi) and Non-distilled" (jand, Chhyang, Tumba). Rice, wheat, barley, millet, maize, fruits and sugar were the commonly used ingredients to prepare alcohol. We found that the median ethanol concentration in homebrewed alcohol was 14.0% )IQR: 10.0-19.0) for distilled alcohol and 5.2% (IQR:3.5-9.8) for non-distilled alcohol. We found a national prevalence of alcohol consumption ever as 24.7% (95% CI: 21.7-28.0) among married women of reproductive age, that of last 12 months as 17.9% (95% CI: 15.3-20.7) and last 30days (current drinking) as 11.8% (95% CI: 9.8-14.1) . There was substantial variation in current drinking prevalence among the districts ranging from 0.2% to 29.9%. Among the women who drank alcohol in last 12 months, a substantial proportion of them drank home brewed alcoholic beverages (95%, 95% CI: 94.3-97.4).Factors associated with alcohol consumption were no education of only informal education, dalit and janajatis ethnicity, alcohol consumption by husband , home brewing of alcohol and being from mountains. In the second study which looked into alcohol consumption behavior were among pregnant women and mothers with children one year., the study participants were from a mountainous district and consisted largely of a specific group of women predominantly from janajati ethnicity. We found that among the total women 34%(95% CI: 30.5-37.3) drank alcohol during pregnancy and 43% (95% CI: 39.4-47.4) drank during postpartum period. Nearly all (99%) drinking women , mostly consumed alcohol 35%(95% CI: 29.2-41.1) consumed it daily during pregnancy, While 74%(95% Ci: 68.8.79.6) consumed daily during postpartum period. Of currently drinking women,21% (95%CI: 16.7-26.7) drank _>5standard drinks on average per day in the last 30 days. No or low level of education, Absence of knowledge that alcohol during pregnancy affects mother and child, being dalits, disadvantaged and janajatis, having a drinking husband and home brewing of alcohol were significant predictors of alcohol consumption during pregnancy and postpartum period. Among the 164 pregnant women ,21.3% (95% CI: 15.7-28.3) had anxiety and 23.8% (95% CI: 17.8-31.0) had depression, with proportion of co-morbid anxiety and depression being 14.6% (95% CI: 10.0-21.0). Similarly, of the 567 women with children under one year 18.7%(95% CI: 15.7-22.1) had anxiety and 15% (95% Ci12.4-18.4) of them had depression. Proportion of women with co-morbid anxiety and depression was 11.5%(95% CI: 9.1-14.4). Of the total 614 women with children under one year, 47 women within 2 months postpartum were excluded from the analysis with the purpose of excluding post partum depression among pregnant women. Lower education levels, primary source of income being agriculture, animal husbandry of labor; history of unplanned pregnancy: and use of tobacco was associated with the anxiety among mothers with children under one year. History of unplanned pregnancy and non-use of tobacco were two independently associated factors with a depression among these women. We did not find a link between alcohol use and anxiety and depression and this could be because alcohol consumption in the Nepalese context is largely determined by ethnicity and socio-cultural factors. Conclusion; Alcohol consumption was a common practice among married women of reproductive age in Nepal with variation among the subgroups of population. Across the nation, one in every ten women in their reproductive age currently ( last 30days) drank alcohol. On the other hand, in one of the mountainous district in Nepal, one in every three women drank alcohol during pregnancy and two in every five women drank during postpartum period with a substantial heavy drinking pattern and high consumption frequency ( daily drinking-35% during pregnancy,74% during postpartum). Home brewed alcoholic beverages were the most common type of alcohol consumed by the women in Nepal. The median ethanol concentration of these beverages was higher than the commonly available market beers and wine but lesser than the branded liquor such as spirit. This study also found that around one in every five pregnant women and mothers of children under one year from the mountainous district of Sindupalchowk in Nepal had an increased level of anxiety and depression. There is a clear necessity of interventions to reduce alcohol consumption and expliciity stop its consumption by women during their pregnancy as well as by those planning to become pregnant. Finding suggested, increasing awareness about consequences of drinking during pregnancy and postpartum period would be helpful probably as one of the components of routine antenatal care with a special focus to ethnic groups such as dalits, disadvantaged Janajatis including relatively advantaged janajatis well as the women with lower levels of education. Culture sensitive behavior change communication interventions aimed at reducing home brewing and husband's drinking would also important . In addition, targeted health system interventions are needed for improving the psychological wellbeing of women, including pregnant women, as well as newborn health and wellbeing.